Phase envelope calculations of synthetic gas systems with a crossover equation of state - Vinhal, Andre P.C.M.; Yan, Wei; Kontogeorgis, Georgios M. (The Journal of supercritical fluids, 2021)
•PT- and VT-based algorithms for phase envelope calculation using a crossover equation of state based on the renormalization group theory.•Evaluation of the advantages of the VT-based phase envelope algorithm over the common PT-based algorithm that utilizes pressure and temperature as natural variables.•Comparison of the results from both the cubic and the crossover models for 30 synthetic natural gas mixtures. [Display omitted] We describe, in this work, a procedure for the calculation of the phase envelope of multi-component systems using a crossover Equation of State (EoS) based on the renormalization group theory and two different algorithms. The first algorithm utilizes pressure and temperature as natural variables, while the second uses volume and temperature. Our comparison shows that the second method is more suitable to a crossover EoS, as it avoids solving for the volume roots of the EoS, which is computationally intensive and potentially hampers the widespread use of such models in engineering applications. Moreover, we compare the simulated phase envelopes with the experimental data of 30 synthetic natural gas mixtures. The results indicate that the crossover SRK EoS has a similar performance to the classical model. Although larger deviations are observed for the representation of the bubble and dew-point curves, the crossover EoS yields a superior description of the critical points.